2015
DOI: 10.1017/s0373463315000260
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Marine Pilots' Planning and Manoeuvring Skills: Uncovering Mental Models to Assess Shiphandling and Explore Expertise

Abstract: This paper introduces an assessment methodology that can underpin the objective measurement of shiphandling skills and permit comparative analysis of manoeuvring plans against their execution in a full mission bridge simulator. It was hypothesised that expert shiphandlers would have shown a strong consistency between the initial plan provided and the following execution. Ten marine pilots participated in the study. Their performance was evaluated across several variables using data gathered during the planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This human control is also a complicated, often not optimal process, and as such is subject to some randomness. Progress has been made in the research methodology of this field over the decades [10,11]. With the computer revolution and progress in the knowledge of ship manoeuvring hydrodynamics, an FMBS has been widely introduced to studies aimed at the harbour and waterway design or improvement of operational performance of ship and crew.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This human control is also a complicated, often not optimal process, and as such is subject to some randomness. Progress has been made in the research methodology of this field over the decades [10,11]. With the computer revolution and progress in the knowledge of ship manoeuvring hydrodynamics, an FMBS has been widely introduced to studies aimed at the harbour and waterway design or improvement of operational performance of ship and crew.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Darbra et al, 2007;Bruno and Lützhöft, 2009;Lahtinen et al, 2020), only a limited number of studies have explored task design, knowledge and expertise in this domain (e.g. Orlandi, Brooks and Bowles, 2015;Butler, Read and Salmon, 2022). Therefore, little is known about what characterizes expertise and expert knowledge within this domain.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, human factor specialists work in these two fields addressing issues concerning the relationship between humans and technology, such as simulators (Lützhöft et al 2017). Related to these two areas, studies in the maritime domain can be found in a variety subjects, such as organizational studies of marine operations (Weick 1987) and assessment of technology (Lützhöft et al 2010a, b;Nilsson et al 2008Nilsson et al , 2009Orlandi et al 2015). Through the study of these issues as they pertain to organizations, researchers aim to determine ways to train humans to be reliable assets for an organization.…”
Section: Introductionmentioning
confidence: 99%